2003
DOI: 10.1021/ol0353868
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Efficient Microwave-Assisted Amination of Electron-Rich Aryl Halides without a Transition-Metal Catalyst

Abstract: [reaction: see text] A rapid and direct amination of aryl halides has been developed in good to high yields under microwave irradiation without a transition-metal catalyst. This reaction is a particularly powerful method for the coupling of electron-rich aryl halides with various amines. In some cases, the excellent regioselectivity could be observed, which facilitated the preparation of meta-substituted anilines from ortho- or para-substituted phenylhalides. In addition, a mechanism via the interesting benzyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 15 publications
5
78
0
Order By: Relevance
“…Preliminary mechanistic investigations point towards an unusual hybrid reaction pathway that exhibits features of both radical and aryne intermediates. Although Daugulis and Tu have reported a limited number of basepromoted C2-and N-selective arylation reactions of indoles, [30][31][32] there appear to be very few precedents for C3-selective variants [32,33] and none that proceed by the proposed hybrid radical/aryne mechanism. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary mechanistic investigations point towards an unusual hybrid reaction pathway that exhibits features of both radical and aryne intermediates. Although Daugulis and Tu have reported a limited number of basepromoted C2-and N-selective arylation reactions of indoles, [30][31][32] there appear to be very few precedents for C3-selective variants [32,33] and none that proceed by the proposed hybrid radical/aryne mechanism. …”
mentioning
confidence: 99%
“…The fact that O 2 leads to greater amounts of N-arylated products is consistent with literature precedent. [30] In contrast, the electron transfer inhibitor p-dinitrobenzene, completely suppresses C3 arylation (Table 4, entry 4), with only minimal amounts of N-arylated product formed. This result strongly implicates the role of electron transfer processes in the reaction mechanism.…”
mentioning
confidence: 99%
“…This suggested that PEGs acted not only as the solvent but could accelerate the coupling reactions. [14] Looking through the published papers, it can be seen that Tu [19] has reported the rapid and efficient microwave-assisted amination of electron-rich aryl halides without a transition-metal catalyst and Leadbeater [20] also disclosed an example of the transition metal-free Sonogashira-type coupling. Therefore, in this paper we have shown that Suzuki-Miyaura coupling reaction could be carried out without using a transition metal catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…N-(3-Hydroxyphenyl)-morpholine [18] (product in Table 1 and Table 2 3-Hydroxy-N-methyl-diphenylamine [19] ( Table 2, 156.7, 150.8, 149.0, 130.3, 129.6, 122.7, 122.6, 111.7, 107.8, 106.2, 40.6. N-(3-Hydroxyphenyl)-piperidine [20] ( Table 2, entries 2 and 27): N-(4-Hydroxyphenyl)-morpholine [6] ( Table 2, 4-Hydroxy-N-methyldiphenylamine [6] ( N-(4-Hydroxyphenyl)-piperidine [21] ( [6] ( 4'-(N-Phenyl-N'-methylamino)-acetophenone [25] ( 3'-(N-Phenyl-N'-methylamino)-acetophenone [6] ( 4-(N-Phenyl-N'-methylamino)-benzamide [28] ( N-tert-Butoxycarbonyl-4-(4-hydroxyphenyl)-piperazine [30] ( …”
Section: General Procedures For the Coupling Of Aryl Halides With Aminesmentioning
confidence: 99%